Nitric oxide as the main multifunctional regulator of immunocompetent and endothelial cells - Sadlyak, O.V.; Kolishetska, M.A.; Baida, M.L.; Musij-Sementsiv, Kh.G.; Sementsiv, N.G.; Lesyk, R.B. (Вiopolymers and Cell, 2017)
Nitric oxide (NO) plays an important role in metabolism. Consequently, every tissue of our body is affected by changes in concentrations of nitric oxide and its metabolites. Here we analyze phenotypic effects of NO and its metabolites in macrophages, NK-cells and lymphocytes that perform protection of the host organism against malignant tumors and intracellular pathogens. Immune system imbalance may result from misregulation of NO synthesis. Nitric oxide also plays an important role in endothelial dysfunction including inhibition of platelet adhesion and aggregation, vasoconstriction and vasodilation disorders of blood vessels, blood rheology changes and the development of atherosclerotic plaques. Thus an imbalance in the synthesis of nitric oxide in the vascular endothelium may be an early marker of lesions of various origins.